COCKAYNE SYNDROME: ROLE OF GENETIC COUNSELLING - Padmalayam, Prajod; Balan, Preethi; Sapkal, Ramshi (Journal of Ayub Medical College Abbottabad, 2015)
Cockayne’s Syndrome (CS) is a rare autosomal recessive disorder characterized by deficiency in the transcription-couple DNA repair pathway caused by mutations in the genes ERCC6 in 65% of individuals and ERCC8 in 35% of individuals. Here we report a rare case of Cockayne’s syndrome in a girl who presented with hallmark features specific to the syndrome. Dissemination of our knowledge about clinical manifestations encountered in Cockayne syndrome is instrumental not only for early evaluation and treatment to prolong life expectancy, but also to initiate early genetic counselling with parents concerning future pregnancies.